El desarrollo de las villas y pequeñas ciudades en los espacios periféricos agrarios: el caso gallego - Rodríguez, Román (Geographicalia, 2017)
The inclusion of Galicia in the occidental economic context has developed a process of urbanization based on the population spacial concentration and their activities, as well as the diffusion of the urban way of life. This fact supposes a chance towards patterns of territorial organization, where little cities and villas are involved in the economic progress of the more undeveloped rural areas.